ANALISIS CITRAAN DALAM ANTOLOGI PUISI RUMAH CINTA KARYA PENYAIR JAMBI - Nindi Riski Marsela; Sumiharti Sumiharti; Uli Wahyuni (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
This research uses descriptive qualitative method. The data is taken from words or sentences and utterances which consist of imagery in the poetry anthology Rumah Cinta by penyair Jambi poet. Poetry is created based on observation that is recorded by senses to make images thought. The image of thought that can see, listen, feel, what it feels by the poet called imagery. From poetry, poet can reveal the bad and good things that they feel so that every poet can create more than two poetry. Moreover that poetry can be collected in a form of book. The book which consists of poetry collection that is created is called poetry anthology. Based on the result of this research, the most dominant imagery that is used by the poetry anthology Rumah Cinta by Jambi poet is imagery of sight. There are 30 utterances that are found and 3 utterances of imagery of movement.Key Word: image, poetry anthology